CFD and wind tunnel testing for a rear car spoiler / Ahmad Azlan Asri - Asri, Ahmad Azlan (2010)
In the way of designing a car, the aerodynamic must taken into consideration so that the car performance and stability will be satisfied and the fuel consumption can be reduced. To achieve this goal, one of the ways is the rear spoilers have to install at the rear end of car. The spoiler can create down force to allow the car grip on the road for better car stability. However, the position of the spoiler also have to chosen correctly to make the car aerodynamic acceptable. So, this study focused on the effect of rear spoiler on the sedan car in terms of drag coefficient and lowering fuel consumption. The method employed for this analysis by using Computational Fluid Dynamics (CFD) software and UiTM Low-Speed Wind Tunnel. The 1/17 scale of car prototype is drawing by using CATIA V5R18. Three variable data were tested such as velocity (v), height of spoiler (h), and angle of attack (a). The car then will simulated without using rear spoiler to compare the effect. Drag Coefficient (Cd) and Lift Coefficient (CI) were determined during simulation and experimental progress. The result will be investigated by applying the Fluid Mechanics relations to understand the situation. From the results, the comparison will be made either to choose the car without rear spoiler or a car with rear spoiler. After that, the best rear spoiler which can give less drag and fine down force was chosen. For the expected result, the scale car without rear spoiler will give large drag compared the car with rear spoiler. Then, the lower height and negative angle of attack is will generate more drag. The data that give the less drag was considered as achieved the objective of this project which is to reduce fuel consumption